Al-Marzibani and its impact on intellectual life in the fourth century AH (Journal of the College of Basic Education, 2022)
Al-Marzibani contributed effectively to the enrichment of the Islamic library with many books that had an effective impact in reviving intellectual life in the fourth century AH, and this is not evidenced by his abundant, rich and noble production. And his writings testify that he is part of the scholarly life, such as one who devotes himself to it and is not preoccupied with anything else. From strength, durability, depth, sculpture and thinking, and evidence of his constant contact with his scientific life on the one hand, and evidence of his grace and fertility on the other hand. With this scale, the knowledge and virtue of a man is outweighed, then the excellence of what he wrote is outweighed.